2021
DOI: 10.3390/plants10091778
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk of Melatonin and Hydrogen Sulfide Determines Photosynthetic Performance by Regulation of Carbohydrate Metabolism in Wheat under Heat Stress

Abstract: Photosynthesis is a pivotal process that determines the synthesis of carbohydrates required for sustaining growth under normal or stress situation. Stress exposure reduces the photosynthetic potential owing to the excess synthesis of reactive oxygen species that disturb the proper functioning of photosynthetic apparatus. This decreased photosynthesis is associated with disturbances in carbohydrate metabolism resulting in reduced growth under stress. We evaluated the importance of melatonin in reducing heat str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 108 publications
3
60
0
2
Order By: Relevance
“…The result is an activation of the metabolic turnover such that it is adequate and conditioned to the physiological situation of the moment. In summary, melatonin has multiple regulation actions; for example, it influences photosynthesis, improving the efficiency of Rubisco and other Calvin cycle-related enzymes, Photosystem I and II, chlorophyll and carotenoid content and stomatal complex, with the result of a higher net photosynthesis, and, in specific carbohydrate metabolism, melatonin mobilizes some key pathways such as starch and sucrose biosynthesis, through SPS, SuS, and invertases upregulation, mainly (see Figure 3), increasing biosynthesis sugar rate to cope with stressful situations [99].…”
Section: Discussionmentioning
confidence: 99%
“…The result is an activation of the metabolic turnover such that it is adequate and conditioned to the physiological situation of the moment. In summary, melatonin has multiple regulation actions; for example, it influences photosynthesis, improving the efficiency of Rubisco and other Calvin cycle-related enzymes, Photosystem I and II, chlorophyll and carotenoid content and stomatal complex, with the result of a higher net photosynthesis, and, in specific carbohydrate metabolism, melatonin mobilizes some key pathways such as starch and sucrose biosynthesis, through SPS, SuS, and invertases upregulation, mainly (see Figure 3), increasing biosynthesis sugar rate to cope with stressful situations [99].…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic effects of melatonin and H 2 S regulated K + /Na + homeostasis, and reduced excessive accumulation of ROS by enhancing the activity of antioxidant enzymes. Inhibition of H 2 S by HT reversed the melatonin-modulated heat tolerance by inhibiting photosynthesis, carbohydrate metabolism, and the activity of antioxidant enzymes in wheat [36]. Recent investigation has revealed that melatonin-induced pepper tolerance to iron deficiency and salt stress was dependent on H 2 S and NO [118].…”
Section: Crosstalk Of Melatonin and H 2 S In Plantsmentioning
confidence: 99%
“…Various pharmacological, enzyme activity, and gene expression investigations revealed the crosstalk of H 2 S-melatonin in response to salt and heat stress in tomato and cucumber [34][35][36]. Exogenous melatonin induced the H 2 S generation by activating the L-cysteine desulfhydrase (L-CDes) activity, which was encoded by LCD, DCD, and DES1 [31,35].…”
Section: Pharmacological Genetic and 'Omics' Approach To Understand The Crosstalk Of H 2 S-melatonin During CD Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous melatonin also induces the production of endogenous NO which antagonizes ethylene biosynthesis and, henceforth, delays senescence [194]. Melatonin, along with H 2 S, helps in mitigating high temperature stress by improving photosynthetic attributes and carbohydrate metabolism [64]. Besides reducing accumulation of indole-3-acetic acid, melatonin (20 µM) application in Oryza sativa grown under fluoride stress hinders fluoride uptake and alters the phytohormone homeostasis [72].…”
Section: Melatonin Crosstalk With Phytohormones Under Abiotic Stressesmentioning
confidence: 99%